Charge distribution in turbostratic few-layer graphene studied by carbon isotope labeling. (15th April 2022) - Zhuang, Pingping; Liu, Jing; Huang, Junjie; Dou, Chao; Cai, Weiwei; Lin, Weiyi
Abstract: Elucidating layer-resolved charge distribution in van der Waals stacked crystals is crucial for electronic applications based on 2D materials. Here, we use CVD-grown few-layer graphene (FLG) labeled by carbon isotopes as a prototype, in which Raman features of two isotope components identify distinct layers. Electrical transfer characteristics of graphene field-effect transistors (GFETs) are employed to quantitatively calibrate the correspondence of Fermi level and G-phonon frequency that shifts with the charge-carrier concentration ( n ) variation. The isotope-assisted spectroscopy reveals previously unprobed characteristics that the n value of both top and bottom layers in FLG is close rather than following an exponential decay law. This negligible gradient likely benefits from the π − π interaction that favors the interlayer diffusion of charges. In addition, each extra layer reduces the degree of charge exchange at the graphene/dopant interface. These results have important implications for FLG nanoelectronics and provide a robust framework by which one can further investigate the critical properties of other 2D systems. Graphical abstract: Image 1